Controversy of Presidential Decrees in a State of Emergency in Indonesia: Case Study of The Decrees of President Soekarno And President Abdurrahman Wahid - Aninda Novedia Esafrin; Qurrota Ayuni, S.H., MCDR (Jurnal Penelitian Hukum De Jure, 2022)
The debate of the decrees of President Soekarno and President Abdurrahman Wahid regarding the constitutional and unconstitutional presidential decree in emergency constitutional law continues to be a controversy that does not end until now because it is still being discussed related to the situation. This paper discusses 2 (two) phenomenal decrees related to constitutional or unconstitutional in terms of emergency constitutional law. By using normative juridical research methods. The approaches used are the statutory approach, the conceptual approach, and the historical approach. This paper discusses 3 (three) main findings, among others: First, the Presidential Decree is de facto and de jure motivated by no recognition of political action or legal action; Second, the decree is formally regulated in Article 12 and Article 22 of the Constitution of the Republic of Indonesia because in the 1945 Constitution it is regulated that if the country is in a state of danger, the president can make decisions in accordance with the authority regulated by laws and regulations; and Third, The decree can be said to be unconstitutional because it is not in accordance with the Indonesian constitution. The decree is not regulated by Indonesian legislation so that formation is considered unconstitutional because it cannot be based on law. However, in the emergency constitutional law, this situation becomes normal because the emergency constitutional law does not use legislation as usual when the country is in normal condition.